Is the Elephant Stepping on its Trunk? The Problem of India's Unbalanced Growth - Robin Douhan; Anders Nordberg (Research Institute of Industrial Economics (IFN), 2008)
It is often assumed that recent success in the high-technology software industry will lead India's development. However, evidence suggest that basic manufacturing industry is stagnant. This paper proposes a mechanism that ties these two trends together. A big-push type of model, featuring linkages between firms, demand spill-over, and technology choice is elaborated. By imposing different cost structures on the manufacturing and high-technology industries the model describes outcome in terms of distribution between sectors. It is found that a policy which promotes a high-technology sector can have negative effects on the manufacturing industry as well as aggregate income. Directing resources towards infrastructure, on the other hand, benefits all sectors and increases aggregate income. The results from the model are found to correspond with the recent development pattern in India.
Keywords: L16; O14; O25; 330; Industrialization; India; Industrial Structure; Industrialisierung; Industriestruktur; Hochtechnologiesektor; Verarbeitendes Gewerbe; Wirtschaftswachstum; Indien